Advance oxidation processes of Rhodamine B under O3/UV using spent bleaching earth-ZnO composite: Performance in kinetics - Andriyan Yulikasari; Ervin Nurhayati; Fransiscus Xaverius Fernando Cornelio; Diah Susanti (Sustinere: Journal of Environment and Sustainability, 2023)
Spent bleaching earth and ZnO composite (SBE/ZnO) was prepared as the catalyst for the advanced oxidation processes (AOPs) of rhodamine B (RB) under O3/UV.  The photocatalytic ozonation process of RB was conducted at an ozone flow rate of 1 L/min by adjusting the variation of initial RB concentration, catalyst dosage, and reaction time.  The RB removal efficiency of 96.7% was reached within 36 min at optimal operational conditions (initial concentration of 100 mg/L and catalyst dosage of 1.5 g). The kinetical analysis at this condition showed that the photocatalytic ozonation process of RB followed a pseudo-first-order reaction with a rate constant of 0.0975 min-1. Meanwhile, the effect of operational variables was evaluated using response surface methodology (RSM) and resulted in an optimized model for RB Removal following equation:  RB Removal = 84.95 - 6.24A + 5.81B + 22.45C + 3.07AB + 13.14AC - 6.72BC + 0.1174A2 + 7.86B2 - 8.90C2, where A is the initial concentration of RB, B is catalyst dose and C is reaction time, with a high coefficient of determination R2 = 0.9432.